A tutorial on one way analysis of circular linear data. - Anderson-Cook, Christine M. (Journal of Quality Technology)
Some industrial applications lead to observations that are characterized by a bivariate response where one observation is an angle or direction and the other is linear. These data are frequently called cylindrical data since they can be represented by points on a cylinder of radius one. In these industrial applications when several related, but distinct groups produce data of this variety, the analyst often needs to study the common and distinct features of the data across the groups. This paper presents a method for testing whether different functional forms of the relationship between components are required and two strategies for determining an appropriate final model. The goal of both of these strategies is the parsimonious characterization of the data, while preserving the unique characteristics of the groups. A constructed example is presented to illustrate the methodology.